Validity of Cultures of Fluid Collected through Drainage Catheters versus Those Obtained by Direct Aspiration - Everts, Richard J. (American Society for Microbiology, 2001)
To examine the validity of cultures of fluid collected through drainage catheters, we reviewed retrospectively fluid specimens that had been collected through catheters in place for at least 2 days. These specimens were taken from patients at a large tertiary-care hospital. A total of 974 specimens representing 620 patient episodes were received. For 554 (89%) episodes there was no reliable imaging evidence for localized infection, rendering the results uninterpretable. The remaining 66 (11%) episodes were followed within 2 days by radiologically guided or open aspiration of one or more fluid collections (predominantly in the abdomen or pelvis) near the drainage catheter, allowing comparison of culture results of 59 direct aspirates with those of prior catheter drainage. In 33 (56%) of these 59 cases, matched culture results were equivalent for therapeutic decision making. However, relying on results of catheter drainage cultures would have led to inadequate antimicrobial therapy in 13 (22%) cases, to excessive therapy in 11 (19%) cases, and to both in 2 cases (3%). We conclude that radiological imaging should be standard practice in the assessment of deep-tissue infections in patients with drainage catheters, and that direct aspiration of potentially infected fluid collections is the most reliable method of obtaining specimens for culture that should be used to guide therapy.